Levonorgestrel-releasing intrauterine system vs. systemic medication or blank control for women with dysmenorrhea: Systematic review and meta-analysis of randomized controlled trials - Jing Wang; Ke Deng; Ling Li; Yi Dai; Xin Sun (Frontiers Media S.A., 2022)
AimsTo compare efficacy and safety of the levonorgestrel-releasing intrauterine system (LNG-IUS) with systemic medication or blank control in the treatment of dysmenorrhea.MethodsPubMed, EMBASE, the China National Knowledge Infrastructure (CNKI) and Wanfang Data were searched to collect randomized controlled trials (RCTs) comparing LNG-IUS with systemic medication or blank control among women diagnosed with primary dysmenorrhea or secondary dysmenorrhea (adenomyosis or endometriosis) from inception to 2020.04. Der Simonian-Laird random-effect model was used to pool data.ResultsSeventy-one RCTs (6551 patients) were included. Overall bias risk was medium. Sixty-two articles enrolled patients with adenomyosis; LNG-IUS significantly reduced the visual analogue scale (VAS) score compared with the systemic medication group among adenomyosis women at 3 months (standardized mean difference (SMD) = −0.81, 95% confidence interval (CI) −1.22 to −0.40); 6 months (SMD = −1.25, 95%CI: −1.58 to −0.92); 9 months (SMD = −1.23, 95%CI: −1.63 to −0.83); 12 months (SMD = −1.66, 95%CI: −2.14 to −1.18). No difference was found in the incidence of irregular vaginal bleeding (16 RCTs; RR = 0.91, 95%CI: 0.62−1.33, P = 0.63, I2 = 4%) and other adverse outcomes. Sensitivity analysis regarding randomization methods was robust. Nine RCTs enrolled endometriosis women. Pooling results showed no significant difference between LNG-IUS and systemic medication treatment in terms of VAS at 6 months (SMD = −0.27, 95% CI: −0.97-0.43). Moreover, LNG-IUS was associated with higher risk of irregular vaginal bleeding (26.8% vs. 0).ConclusionsLNG-IUS was associated with a reduced severity of dysmenorrhea compared with systemic medication; it was also beneficial for better control of menstrual blood loss and fewer adverse outcomes. Owing to small sample sizes, further well-designed RCTs are warranted to confirm these findings and long-term effects of LNG-IUS in the treatment of dysmenorrhea. Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier: CRD42021228343.